The rise and falter of the field of ethnic politics in Australia - Tabar, Paul (2016)
Since the advent of multiculturalism in Australia in the 1970s, ‘ethnicity’ has acquired not only cultural and social importance, but significant political consequences as groups mobilised around ‘ethnic communities’ and as the State increasingly structured social policy around cultural differences. The political patronage and funding central to Australian multiculturalism led to the development of organisations and leaders whose task was not only to service the needs of specific ‘ethnic communities’ but to represent them in the wider political field. This paper traces the emergence in Australia of the field of ethnic politics, in the Bourdieusian sense. Using the Lebanese ‘ethnic community’ as a case study, we analyse the accumulation by ‘community leaders’ of ‘ethnic capital’, which converts to symbolic capital that is recognised by the State as the capacity of leaders to represent ethnic communities. We argue that conflicts arising over moral panics around ‘Lebanese youth gangs’ in Sydney since 1998 have undermined the legitimacy of Lebanese community leadership. This has coincided with moves by the NSW government to devalorise ‘ethnicity’ and substitute it with ‘communal relations’, which accord with the national shift away from multiculturalism under the Howard government, as the politics of ‘One Nation’ are increasingly mainstreamed.